Prevalence and factors associated with emotional and behavioural difficulties among children living with HIV in Malawi: A cross-sectional study - Kendall, Garth; Ali, Mohammed; Kalembo, F.; Chimwaza, A. (BMC, 2019)
Background: Approximately 84,000 children under the age of 15 years are living with HIV in Malawi. Although the survival rate of children living with HIV in Malawi has improved due to the increased availability of antiretroviral medications, these children continue to experience numerous challenges negatively impacting on their mental health. The aim of this study was to investigate the prevalence of, and factors associated with, emotional and behavioural difficulties in children aged between 6 and 12 years living with HIV in Malawi. Methods: A random sample of 429 primary caregivers of children living with HIV drawn from the three main administrative regions of Malawi was recruited in a cross-sectional study. They completed a questionnaire about family socio-demographic characteristics, HIV disclosure, and child demographic and clinical characteristics, as well as the Strengths and Difficulties Questionnaire, Life Stress Scale, Support Function Scale, and Impact on Family Scale which were pre-tested and translated into the local Chichewa language. Data were analysed using descriptive statistics and logistic regression. Findings: Using the newer band categorisations of the Strengths and Difficulties Questionnaire, parent version, 31% of primary caregivers reported that their child had a slightly raised to very high level of total difficulties. Factors that were associated with difficulties were: primary caregivers' young age (adjusted odds ratio [aOR] 3.6; 95% confidence interval [CI]: 1.4-9.5); low level of education (aOR 2.6; 95% CI: 1.2-5.7); lack of employment (aOR 2.7; 95% CI: 1.2-5.9); the report of a substantial impact of the child's illness on the family (3.1; 95% CI: 1.5-6.5); and a low level of family functional support (aOR 2.0; 95% CI: 1.1-4.1). Neither non-disclosure of HIV status nor any of the child demographic or clinical factors were significant in multivariate analysis (p >.0.05). Conclusion: Close to one-third of children living with HIV in this study had high scores indicative of emotional and behavioural difficulties. Emotional and behavioural difficulties in children living with HIV were associated with family demographic and psychosocial factors, but not HIV disclosure. Effective policies and programs that promote the mental wellbeing of children living with HIV in Malawi are indicated.